Seroprevalence of an antibody against diphtheria, tetanus, and pertussis among the elderly in Khon Kaen, Thailand - Teeraporn Chinchai; Nawarat Posuwan; Viboonsak Vuthitanachot; Nasamon Wanlapakorn; Yong Poovorawan (BMC, 2019)
Abstract Background Owing to a declining birth rate and longer lifespan, the number of elderly people (≥ 60 years) in Thailand has grown rapidly. However, the elderly are at significant risk of infectious diseases because they have never been immunized, because they have not been completely immunized, or because their immunity has waned. Immunity against infectious diseases in the elderly is an important means of controlling diseases in the community. Our objective was to evaluate the seroprotective rate against diphtheria, tetanus, and pertussis in the elderly Thai population. Methods In total, 430 healthy individuals from the northeastern region of Thailand were enrolled in this study and stratified into five age groups: 60-65, 66-70, 71-75, 76-80, and > 80 years. Serum samples were collected and quantitatively analyzed for diphtheria, tetanus, and pertussis IgG antibody by using commercial ELISA kits. For anti-diphtheria toxoid and anti-tetanus toxoid ELISA, values < 0.01 IU/ml were interpreted as seronegative, and for anti-Bordetella pertussis toxin ELISA, values < 5 IU/ml were interpreted as seronegative; these definitions were in accord with previous studies. Results For diphtheria toxoid Ab, the majority of the population had antibody levels > 0.01 IU/ml. For tetanus anti-toxoid Ab, the majority of the population had antibody levels of > 0.01 IU/ml, of which approximately 34% had durable antibody protection levels (DAPL) of ≥ 1 IU/ml. Meanwhile, nearly 45% of the population had an Ab level against pertussis lower than the protectivity level. Conclusions In total, 97.2%, 83.5%, and 55.8% of the population had a higher antibody level than the minimal protective level for diphtheria, tetanus, and pertussis, respectively. In order to prevent an outbreak of these diseases in the future, the elderly should be administered with Tdap revaccination to provide diphtheria herd immunity in the population; this will increase cocoon phenomenon for pertussis and protect the population from tetanus-prone injury.